Visitors and physical development carrying capacity in Malaysian Marine Parks - Othman, Fadina; Yahya, Khairun; Mohamed, Badaruddin (2013)
Over the years, the emphasis of tourism development in protected areas is changing from providing quantity in the development of facilities to the provision of quality that are appropriate and compatible for visitors. This concern for quality focuses on issues that include maintaining the intrinsic appeal of the area, the promotion of compatible tourism facilities at a scale that is appropriate to the designated area, its carrying capacity, and the way of life among the local communities. Tourism planning in protected areas such as marine parks is about managing its visitors and the type of physical development that would eventually be about maximizing the benefits while minimizing its cost. Planning should identify strategies that would render the development of tourism as less of a spontaneous process, but more of a coordinated vehicle for development. The aim of this paper is to explore the approaches that can be taken by the authorities managing the marine parks of Malaysia on the alternative and sustainable solutions in managing this type of protected areas. The findings and discussion segment propose the Visitors Management for managing the visitation and Physical Development Management for managing the physical development of these protected areas. To adhere to the carrying capacity of these two elements is crucial as marine parks require extensive monitoring to ensure its sustainability and preservation. The researcher has list the approaches of carrying capacity practices with regards to visitors’ management and development carrying capacity in Malaysian Marine Parks as recommendations.